PENYAKIT - PENYAKIT PENYEBAB DEMAM PADA ANAK PENDERITA KEJANG DEMAM DI RS HAJI MEDAN PERIODE 2019 - 2020 - MUTIARA YUSFAH PUTRI S; ANCE ROSLINA (JURNAL ILMIAH MAKSITEK, 2021)
Infectious diseases are still found in children. It can manifest into seizures as a result of high fever. To find out the diseaseswhich cause fever in children with febrile seizure in Haji Hospital Medan. This is a descriptive observational study.The most frequent disease which causes febrile seizure were upper respiratory tract infections which were found in 34children (44,73%). Based on age, 70 children (53,43%) aged 1-2 years old had febrile seizure and based on gender, 79children (60,3%) were boys and 52 (39,69%) were girls. Febrile seizure was mostly found in children with upper respiratorytract infections, aged 1-2 years old and were mostly found in children.